Implementasi Permendagri Nomor 70 Tahun 2019 Tentang Sistem Informasi Pemerintah Daerah (SIPD) Di Kabupaten Sekadau - Dedi Irawan; Martoyo Martoyo; Herlan Herlan (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to examine the implementation of the Regulation of the Minister of Home Affairs (Permendagri) Number 70 of 2019 concerning the Regional Government Information System (SIPD) in Sekadau Regency. SIPD is an essential tool for achieving transparent, accountable, and efficient government administration, particularly in managing regional finances. However, the implementation of SIPD in Sekadau Regency still faces various challenges and obstacles that affect its effectiveness and efficiency. This research employs a qualitative approach with a descriptive method to describe the SIPD implementation process and the factors influencing its success. Primary data were obtained through in-depth interviews with key informants, including officials from the Regional Financial and Asset Management Agency (BPKAD) of Sekadau Regency and related agencies, while secondary data were collected from policy documents, reports, and official data related to SIPD implementation.The results indicate that the implementation of SIPD in Sekadau Regency has not yet been optimal. The challenges include limited information technology infrastructure, a lack of trained human resources, coordination issues between government units, and insufficient political support. Additionally, resistance to change and conventional work habits have also hindered the full application of SIPD. To address these obstacles, it is necessary to enhance human resource capacity, strengthen technological infrastructure, improve inter-organizational communication, and secure stronger political support.This study contributes to the development of public administration knowledge and provides practical recommendations for local governments to improve SIPD implementation strategies. The implications of this research emphasize the importance of a comprehensive approach and effective coordination among various stakeholders to achieve better governance.